Dynamic terahertz polarization in single-walled carbon nanotubes - Xu, X; Parkinson, P; Chuang, K; Johnston, M; Nicholas, R; Herz, L (2010)
We have investigated the anisotropic dynamic dielectric response of aligned and well-isolated single-walled carbon nanotubes using optical-pump terahertz (THz)-probe techniques. The polarization anisotropy measurements demonstrate that the THz radiation interacts only with radiation polarized parallel to the nanotubes which have been selectively excited by a polarized pump pulse thus allowing controlled THz polarization to be achieved from unaligned nanotubes. © 2010 The American Physical Society.